Interpretation Of Judges In Supreme Court Decision Number: 46 P/HUM/2018 - Muslim Andi Yusuf; Dharma Fidyansari (Susbtantive Justice International Journal of Law, 2019)
This research was conducted to determine the interpretation of judges in the Supreme Court Decision No. 46 P/HUM/2018. This study uses a normative type of research with an approach to identifying legislation and literature that is relevant to research. Data collected from primary, secondary, and tertiary legal materials are analyzed qualitatively, arranged systematically, and presented descriptively. The results of this study indicate that in the Supreme Court Decision Number 46 P/HUM/2018 which judges that Article 4 paragraph (3), Article 11 Paragraph (1) Letter d and Appendix Model B.3 Election Commission Regulation Number 20 of 2018 is contradictory to Law Number 17 of 2017 concerning General Election in conjunction with Law Number 12 of 2011 concerning Formation of Regulations and Judges’ Considerations based on the interpretation of the testing object test stones namely the sentences in the text of Law Number 7 of 2017 concerning General Elections and Law Number 12 of 2011 concerning Formation of Legislation as a guide so that the interpretation of judges is based on exploring the meaning contained in the statement written norm text by studying the book in sentence structure or its relationship with other rules.